Anomalous inversion effect of hydraulic properties in contacted asperity fractures: insights from laboratory flow experiments - Gao, Xuefeng; Wang, Hongtao; Ma, Dan; Zhang, Yanjun; Yang, Haiyan; Huang, Yibin (Frontiers in Earth Science, 2025)
Multi-physics modeling of underground rock mass fractures rarely accounts for contact asperities, thus hindering fracture-related permeability estimation during geofluid migration processes. Here we present a novel method for preparing contact-type fractures, employing a random placement technique to reconstruct a random array of contact asperities in fractures with varying contact ratios. We investigate the hydraulic evolution of fractures with random contact asperities under confining pressure. We reveal that the sensitivity of permeability decay with increasing stress is closely related to the contact ratio, with fractures having lower contact ratios exhibiting a significantly greater reduction in permeability compared to those with higher contact ratios. Traditional hydraulic aperture prediction models based on contact rates, which neglect stress, are not applicable with low contact ratios. Furthermore, we observe for the first time that the permeability of contact-type fractures undergoes an inversion effect with increasing contact ratio, manifested as an anomalous positive correlation between permeability and contact ratio at low contact ratios. We developed an empirical permeability prediction model that incorporates both contact ratio and stress, which accurately captures the permeability evolution in contact-type fractures. These findings open a prospective for characterizing, modeling, and predicting fluid transport in complex underground fracture networks.